PERAN KEPERCAYAAN SEBAGAI PEMEDIASI DAN HAMBATAN BERPINDAH SEBAGAI PEMODERASI PADA PENGARUH KEPERCAYAAN DAN KEPUASAN NASABAH TERHADAP LOYALITAS DI BPR KOTA PEKALONGAN - BIBM., Hons, M.Si, Leni Susanti (Majalah Neraca, 2015)
This research is aquantitative study with survey method on micro banking services company. The purpose of this study was to analyze the role of trust as mediator and switching barrier as moderator in Customer Satisfaction and Loyalty of Rural Banking. The object of this study is trust, customer satisfaction, switching barrier and loyalty. Based on the results of research and data analysis with Structural Equation Modelling (SEM) showed that: (1) There is positive effect between customer satisfaction to trust; (2) There is a positive effect between trust to loyalty from a consumer; (3) Trust mediated the effect between customer satisfaction toÂ  loyalty from a consumer; (4) There is a positive effect between customer satisfaction to loyalty from a consumer; (5) Switching barrier moderated theÂ  effect between customer satisfaction to loyalty from a consumer. Based on the research result, it can be concluded that in general there is a relationship between trust, customer satisfaction, switching barrier and loyalty. Keywords: Trust, Customer Satisfaction, Switching Barrier Loyalty, Rural Banking